Broadband low‐profile transmitarray antenna using three‐dimensional cross dipole elements. Issue 1 (9th October 2018) - Zhong, Xianjiang; Ruan, JiaNing; Lei, Zhiyong; Xu, He‐Xiu
Abstract: This article presents a novel transmitarray antenna using three‐dimensional frequency selective structures as the radiating elements. The proposed unit cell, which consists of two cascaded cross dipoles, has a thickness of 0.22λ0 and provides a 310° transmission phase range with transmission magnitude equal or better than −0.8 dB. Compared with those conventional transmitarray antennas, the proposed one can realize greater flexibility in the installation with less manufacturing complexity. For the purpose of validation, a transmitarray prototype using the proposed elements has been manufactured and tested at X‐band. The peak gain of 25.5 dB is achieved at the frequency of 10 GHz, resulting in an aperture efficiency of 64%. Besides, antenna bandwidth of 10% for 1‐dB gain is achieved in this design.